Doors, entrances and beyond... : various aspects of entrances and doors of the tombs in the Memphite Necropoleis during the Old Kingdom - Roeten, Leo, (Archaeopress Egyptology ;, 2021)
Doors are more than a physical means to close off an entrance or an exit; they can also indicate a boundary between two worlds. This volume considers the Memphite Necropoleis during the Old Kingdom, and proposes that porticos, false doors, niches and mastaba chapel entrances are interconnected in their function as a barrier between two worlds.